Expanding the role of ultrasonography in cardiopulmonary assessment in dromedary camels - Tharwat, Mohamed (Frontiers in Veterinary Science, 2025)
Dromedary camels (Camelus dromedarius) have unique cardiopulmonary anatomy and physiology that pose diagnostic challenges unlike those in other large ruminants and equids. Ultrasonography, as a non-invasive, portable, and cost-effective imaging tool, offers great potential for cardiopulmonary evaluation—especially in field conditions where early detection is crucial. This review article explores the expanding role of ultrasonography in assessing the camel heart and lungs, emphasizing recent advances and key clinical applications. It begins by outlining anatomical and physiological features relevant to ultrasound imaging, including cardiac chambers, valves, and pulmonary structures. Principles of ultrasound physics, equipment choices, scanning techniques, and practical considerations such as animal restraint and probe placement are detailed. Normal ultrasonographic findings are summarized to establish baseline reference values. The review highlights the utility of ultrasonography in diagnosing a range of conditions, including pneumonia, pulmonary abscesses, pneumothorax, pulmonary emphysema, pleural effusion, pleurisy, pleuropneumonia, pericardial effusion, endocarditis, pericarditis, myocardial degeneration, as well as calcified and hypertrophic cardiomyopathy. Comparisons with radiography and CT illustrate ultrasound’s strengths in real-time, bedside diagnosis. Notably, the review identifies a critical gap: the lack of standardized protocols and normative datasets for camelids. Addressing these limitations through clinician training, species-specific guidelines, and research into advanced techniques such as Doppler and contrast-enhanced ultrasonography is essential. This review underscores the need for innovation and collaboration to optimize ultrasonographic diagnostics in camelid cardiopulmonary care.